An investigation of harmonic correction techniques using active filtering - Butt, David (1999)
This thesis presents an investigation of techniques used to mitigate the undesirable effects of harmonics in power systems. The first part of this research develops an effective and useful comparison of alternative AC-DC converter topologies. In particular, a full evaluation of the circuit first proposed by Enjeti (known here as the Texas circuit) with a capacitively smoothed output voltage is made, specifically for operation as a 'clean power' supply interface for a variable speed drive (VSD). This mode of operation has not previously been reported in research literature. Simulation and experimental results verify the performance of the circuit and demonstrate that it draws a current with low harmonic content, but the circuit has a number of problems. This part of the research concludes that the six-switch rectifier is the most viable circuit for operation as a supply interface for a VSD due to its bidirectional power flow capability and its excellent versatility of performance.